Controlled growth of 3R phase tantalum diselenide and its enhanced superconductivity - Deng, Ya (2021)
Transition metal dichalcogenides (TMDs) have become a playground for exploring rich physical phenomena like superconductivity and charge-density-waves (CDW). Here, we report the synthesis of the atom-thin TaSe2 with a rare 3R phase and enhanced superconductivity. The 3R phase is achieved by an ambient pressure chemical vapor deposition (CVD) strategy and confirmed by the high-resolution aberration-corrected STEM. Low-temperature transport data reveal an enhanced superconducting transition temperature (Tc) of 1.6 K in the 3R-TaSe2, which undoubtedly breaks the traditional perception of TaSe2 crystal as a material with Tc close to 0 K. This work demonstrates the strength of ambient pressure CVD in the exploration of crystal polymorphism, highlights a decisive role of layer stacking order in the superconducting transition, and provides fresh insights on manipulating crystal structures to gain access to enhanced Tc.